Pengaruh Pengungkapan ESG Terhadap Nilai Perusahaan - M. Fakhriansyah; Devia Septyani; K.M. Faisal Reza (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
ESG disclosure of company value is a theme in this research. Where ESG disclosure in Indonesia is important and mandatory for companies listed on the stock exchange. The sample for this research is mining sector companies listed on the IDX for the period 2018 - 2023. The SPSS 24 software tool is used to see the relationship between ESG disclosure and company value. The results obtained by ESG disclosure have a positive influence on company value in Indonesia in mining sector companies for the period 2018 - 2023. The results of data processing research provide output results of 27.4% of ESG disclosure variables having an effect on company value. Even though ESG disclosure has less than 50% influence on company value, in fact the implementation of ESG disclosure in the mining sector is expected to be a guideline for sustainable development by considering ESG aspects.